Characterization of Tachyplesin peptides and their cyclized analogues to improve antimicrobial and anticancer properties - Vernen, Felicitas (2019)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/).